INDUCTION OF MORPHOLOGICAL MUTANTS IN MUNGBEAN (VIGNA RADIATA (L.) WILCZEK) THROUGH CHEMICAL MUTAGENS - Khan, S.; Kozgar, M. I.; Goyal, S.; Wani, M. R. (The Nucleus, 2011)
A wide range of morphological mutants were identified in two varieties of mungbean. These mutants involved traits effecting plant height, growth habit, seed and pod. The frequency of morphological mutants differed in different mutagenic treatments and also between the varieties. The highest mutation frequency was noticed in the EMS treated population whereas the lowest frequency was observed SA treatments, HZ treatments being the intermediate. Variety NM-1 gave the broader spectrum and frequency of morphological mutations than the var. PDM-11. Of all the mutant types, maximum occurrence of mutation was observed for plant height.